ANALISIS PENGARUH PERSEPSI ANGGOTA, PARTISIPASI ANGGOTA, KUALITAS PENGURUS DAN PERANAN PEMERINTAH TERHADAP SISA HASIL USAHA ANGGOTA KOPERASI WANITA DI KOTA BENGKULU - Barika Ramli (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
Cooperative is one of a growing economic force in the society to support national economic growth. Cooperatives has strategic role to improve living standards in many of community groups. One type of cooperation is the women cooperation that puts women as main actors of cooperative activity. This study aims to determine how Perceptions Members of Cooperation, Member Participation, Quality Management and the Role of Government Influences Business Profit (SHU) of the Women Cooperation in the Bengkulu.  This study uses secondary and primary data. Analysis technique used is multiple regression analysis. The results showed that the coefficient of determination (R2) is 0.41, meaning that the variable perceptions of members, member participation, quality of management and the role of government has contributed to 41 percent in influencing business revenue, while the remaining 59 percent is influenced by other factors. Additionally The Participation of Members (X2), Quality board (X3) and the role of government (X4) has a significant impact on business profit, while the perception of member (X1) had no significant effect